Legal Reconstruction of the Establishment of Places of Worship in Indonesia: A Legal-Political Analysis within the Framework of Land Use and Spatial Planning Law - Suhadi, Suhadi; Muhtada, Dani; Amal, Andi Gazly Satrya (Journal of Indonesian Legal Studies, 2024)
The establishment of places of worship in Indonesia is a critical issue that intersects with legal and political concerns, yet the regulatory framework governing such establishments remains insufficiently codified. Currently, the guidelines for the establishment of places of worship are outlined in the Joint Regulation of the Minister of Religious Affairs and Minister of Home Affairs Number 9 and Number 8 of 2006 (PBM 2006). However, these regulations are not formal laws and fail to provide adequate legal guarantees and protection for all citizens to practice their religion freely. This study uses a normative juridical approach, employing legal, historical, and conceptual methods to argue that the regulations surrounding the construction of places of worship require a comprehensive legal reconstruction. The research analyzes the issue from a legal-political and land law perspective. From a political-legal viewpoint, it is clear that the PBM 2006 does not align with Indonesia's legal ideals. The regulation contains discriminatory provisions that contradict the principles of a unified state, social justice, democracy, and religious freedom. Places of worship are not only a necessity but also a fundamental expression of belief, guaranteed by the Indonesian Constitution. Therefore, regulations governing the construction of places of worship should be enacted as laws, rather than as ministerial regulations. The study concludes that a formal legal framework for the establishment of places of worship, in the form of a law, is urgently needed. Such a law would ensure equal protection for all citizens and foster social justice, thereby protecting the rights of Indonesia’s diverse population to worship in accordance with their beliefs.